ECO-ENHANCEMENTS: SUSTAINABLE SEWAGE SOLUTIONS FOR TONG’AN’S RURAL COMMUNITIES - Tao , Ming Wang; Chen, Li Jun (International Journal of Civil Engineering and Architecture and Real Estate, 2024)
Rural sewage treatment is an important measure to realize the strategy of rural revitalization and improve the rural living environment. Based on the field survey of the rural domestic sewage network upgrading and upgrading area in Tong 'an District, Xiamen City, this paper considers and summarizes the solutions for each stage of rural domestic sewage upgrading, and gives the countermeasures for the problems in the rural domestic sewage network upgrading project. It is hoped to provide some suggestions and guidance for the improvement and management of rural domestic sewage pipe network in the future